Exploring the Effect of Boarding and Alighting Ratio on Passengers' Behaviour at Metro Stations by Laboratory Experiments. (2nd May 2019) - Seriani, Sebastian; Fernandez, Rodrigo; Luangboriboon, Nattanon; Fujiyama, Taku
Abstract : The objective of this work was to study the effect of the ratio between passengers boarding and alighting on the passengers' behaviour at metro stations. A mock-up of a vehicle and the relevant portion of the platform was built to run a series of simulation experiments at University College London's Pedestrian Accessibility and Movement Environment Laboratory (PAMELA). Different scenarios were tested based on the next generation London Underground trains. The scenarios were classified according to different load conditions. Four types of behaviour are described. In most cases boarding is first, and passengers compete for space to enter the train. In the case of alighting, first passengers are faster than the rest of alighters due to the space available on the platform as boarding passengers give way to those who are getting off the train. In addition, alighters form lanes of flow depending on the number of passengers waiting to board the train on the platform. With respect to the train, if the density inside the train is higher than 4 passengers per square metre, then the flow at the doors starts to decrease. More experiments are needed to study the relationship between platform density and boarding and alighting time.